DURVALUMAB FOLLOWING SEQUENTIAL MULTIMODAL TREATMENT IN LIMITED-STAGE SMALL-CELL LUNG CANCER: A REAL-WORLD CASE REPORT OF SYMPTOM CONTROL AND FUNCTIONAL IMPROVEMENT - A. Abdrashov; A. Akter; N. Nurdinov; S. Almetov; D. Musirali; Y. Yeltay; A. Seisenbay (Yassawi Journal of Health Sciences, 2026)
Durvalumab is an evidence-based consolidation option for limited-stage small-cell lung cancer without progression after concurrent platinum-based chemoradiotherapy. Real-world care may involve sequential treatment, adapted dosing, interruptions, and limited follow-up imaging. Aim. To describe symptoms, functional recovery, treatment exposure, and safety after durvalumab following sequential platinum-etoposide chemotherapy and thoracic radiotherapy. Materials and Methods. This CARE-compliant report reviewed the clinical record, treatment chronology, imaging, ECOG performance status (ECOG PS), symptoms, and adverse events. Written informed consent was obtained. Case Presentation. A 54-year-old current non-smoker with minimal remote tobacco exposure had right-lung small-cell carcinoma recorded as cT2aN1M0, stage IIB. Non-contrast brain MRI on 1 December 2024 reported no intracranial mass. He received six courses of platinum-etoposide followed by sequential thoracic radiotherapy (60 Gy). Durvalumab 500 mg was administered intravenously every 2 weeks. Six infusions were delivered from 3 February to 5 June 2026, with a 66-day gap between infusions 4 and 5. Results. Cough, exertional dyspnea, and chest pain decreased, while ECOG PS improved from 2 to 1. Grade 1 pruritus was managed symptomatically; no grade 3–4 immune-related adverse events were documented. Interim ¹⁸F-FDG PET/CT after four infusions showed predominantly post-radiation thoracic changes and new metabolically active foci in the left acetabulum and C7 vertebral body. Possible progression remained unconfirmed because dedicated follow-up imaging and RECIST-compatible measurements were unavailable. Baseline brain MRI did not report metastases, but sensitivity was limited without contrast and no post-treatment brain imaging was available. Conclusion. Durvalumab was accompanied by symptomatic and functional improvement with acceptable short-term tolerability. PET/CT did not establish an objective response and revealed indeterminate osseous foci requiring confirmation. This case describes treatment feasibility and tolerability but does not demonstrate tumour control or anticancer efficacy.